Application of Artificial Intelligence (AI) in Construction Management: A Systematic Literature Review - Silitonga, Daniel M.; Jin, Oei Fuk (invotek, 2023)
Artificial Intelligence (AI) technology is increasingly being adopted in the construction industry in the current era. AI can be integrated with digital technologies such as Building Information Modeling (BIM), Internet of Things (IoT), and Smart Vision (SV). The integration of AI with digital technology has the potential to enhance efficiency, productivity, accuracy, and safety in construction project. This systematic literature review focuses on studying the implementation of AI in construction management, aiming to assess the current role of AI and anticipate future trends in the field. The findings of systematic literature review reveal that AI has been employed in construction projects for tasks such as estimation, resource management, improvement of workplace safety, material selection, structural analysis, and more. The advancements in digital technology, including the influence of 5G connectivity, have further augmented the sophistication of AI applications in the current era. The systematic literature review also delves into the study of machine learning and deep learning, both of which are pivotal in AI technology for executing predictive tasks, analyses, and automated decision-making. Despite the vast potential of AI, this review identifies various challenges associated with the technology, particularly concerning data security. Most existing studies focus on the limited application of AI in specific domains within the construction industry. To address this gap, this systematic literature review provides a comprehensive literature review on the broader perspective of AI application in construction management.